Alkyne Tagged Raman Probes for Protein by Chemical Modification Approach. Issue 3 (30th January 2017) - Ota, Chikashi; Furukawa, Takahiro; Shima, Kanako; Sano, Satoshi; Kuramochi, Kouji; Tsubaki, Kazunori; Noguchi, Shintaro; Takano, Kazufumi
Abstract: Alkyne probe is one of the useful chemical Raman probes for life science since it has an intense band in a Raman silent region of biomolecules (1800‐2800 cm −1 ) and has a small bulkiness which will not affect the property of the attached molecule. In this paper, we developed the chemical modification method to attach alkyne tagged probe to lysine residues using nucleophilic substitution reaction. We investigated the solvent effect to assess the capability of this newly developed molecular system for the environment sensitive probe. The result of the solvent effect showed that the position of the alkyne band was sensitive to the solvent environment, which indicated the potential to probe the local hydrophobic or hydrophilic environment. In addition, we employed the aromatic substituent effect with the aim of increasing the intensity of alkyne band introducing phenyl groups beside alkyne and succeeded in increasing the intensity of alkyne band over 40 times apparently. On the basis of the property of the attached probe, we worked out the future synthesis strategy to expand this chemical modification to wider applications such as in the cell environment. Abstract : We successfully attached the alkyne tagged Raman probe to lysine residues of lysozyme by chemical modification approach. Both the results of the solvent effect and the aromatic substituent effect on this probe showed the potential to investigate the local hydrophobic or hydrophilic environment with high sensitivity. This newly developed alkyne probe will work powerfully to investigate the specific behavior of proteins in the molecular crowding environments by tracing the selective modified target proteins.